2011
DOI: 10.1007/s11120-011-9709-2
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation in Dunaliella tertiolecta reveals a unique NPQ pattern upon exposure to irradiance

Abstract: Highly time-resolved photoacclimation patterns of the chlorophyte microalga Dunaliella tertiolecta during exposure to an off–on–off (block) light pattern of saturating photon flux, and to a regime of consecutive increasing light intensities are presented. Non-photochemical quenching (NPQ) mechanisms unexpectedly responded with an initial decrease during dark–light transitions. NPQ values started to rise after light exposure of approximately 4 min. State-transitions, measured as a change of PSII:PSI fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
(98 reference statements)
6
9
1
Order By: Relevance
“…We suggest that higher rETRs were enabled in this species because of higher fixation rates by RubisCO at elevated pCO 2 . A similar conclusion was drawn by Ihnken et al (2011aIhnken et al ( , 2011b, who found enhanced rETRs in high CO 2 -acclimated cells of the temperate diatom C. muelleri. Interestingly, such a response was not observed in our tested Chaetoceros species that manifested signs of dynamic photoinhibition independent of the acclimation pCO 2 .…”
Section: Light-dependent Chlorophyll a Fluorescencesupporting
confidence: 85%
See 3 more Smart Citations
“…We suggest that higher rETRs were enabled in this species because of higher fixation rates by RubisCO at elevated pCO 2 . A similar conclusion was drawn by Ihnken et al (2011aIhnken et al ( , 2011b, who found enhanced rETRs in high CO 2 -acclimated cells of the temperate diatom C. muelleri. Interestingly, such a response was not observed in our tested Chaetoceros species that manifested signs of dynamic photoinhibition independent of the acclimation pCO 2 .…”
Section: Light-dependent Chlorophyll a Fluorescencesupporting
confidence: 85%
“…6). Such changes in connectivity were also found in the temperate chlorophyte Dunaliella tertiolecta in response to darklight transitions (Ihnken et al, 2011a(Ihnken et al, , 2011b. In our experiments, p′ values determined at the end of the light phase were below 0.1 in all tested species (Fig.…”
Section: The Impact Of Changes In Connectivity On Photoprotectionsupporting
confidence: 79%
See 2 more Smart Citations
“…Samples were dark-acclimated only very briefly (≤2 s), which will oxidize primary electron acceptors in PSII (Q A − ), but not secondary electron acceptors or the PQ pool (Strasser et al 1995), or relax photoprotective NPQ. Although the rapid phase of energy dependent quenching (q E ) might relax due to a dissipation of the ΔpH-gradient within seconds, xanthophyll cycle-mediated q E requires minutes, as do statetransitions (Müller et al 2001, Ihnken et al 2011a. Residual NPQ in illuminated samples can explain the obvious difference between initial samples, which were dark-acclimated overnight, and samples taken at low PF.…”
Section: Light Intensity Stressmentioning
confidence: 99%